Nanocrystal technology in the delivery of poorly soluble drugs: An overview - Nagarwal R.C.; Kumar R.; Dhanawat M.; Das N.; Pandit J.K. (My University, 2025)
Extensive attempts to overcome problems related to solubility of drugs for maximizing bioavailability at targeted sites in the body have been made. The issue of drug solubility appears to attract the continued interest of pharmaceutical manufacturers. In this context, nanocrystallization has emerged as an important tool. In the present review, the authors discuss the advantages of nanocrystallized drugs and examine the products available in the market as well as drugs in the pipeline using nanocrystal-based formulations, which are being developed by pharmaceutical companies for drug delivery. © 2011 Bentham Science Publishers Ltd.